ANALISIS SIKAP KONSUMEN TERHADAP BERAS IMPOR DI KOTA PEKANBARU - M. Fadli; Novia Dewi; Eliza Eliza (UNIVERSITAS LANCANG KUNING, 2021)
ABSTRACT This research aims to analyze the determining attributes of consumer attitudes in consuming import rice. Imported Rice is a relatively new business entering the Indonesian market, especially Pekanbaru city, so it is necessary to carry out a good strategy to maintain its business. The strategy for distributors is through a market-oriented marketing understanding that requires a good understanding of consumer attitudes. This study used accidental sampling method with 36 respondents and purposive sampling for expert or key person as many as 18 respondents. Data was analyzed using prospective analysis. The results showed the determining attributes of consumer attitudes in consuming and buying imported rice based on quadrant I. Prospective analysis consisting of attributes of taste which are not pulen, cream coloured, discount, medium, type of Beras Kita, plain, price and premium that has a strong influence on consumer attitudes and has a dependence between attributes is low. The implications of marketing development are based on quadrant III which consists of attributes of packaging size of 5 kg, packaging size of 10 kg, number of broken granules, cleanliness of no grain. which has a low influence on consumer attitudes and dependence between high attributes so that it becomes output in the system, this applies as a consideration for the producers what should be improved and improved for the development of marketing Rice Imports. Keywords : Consumer Attitudes, Import Rice, Prospective Analysis